A mixed-methods approach to explore the association between age and medication -related problems among adults - Munshi, Reema Mohammad (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2024)
General introduction Much attention was focused on the ageing phenomenon and how to improve the quality of life in older people. Medication-related problems (MRPs) can potentially lead to hospital admissions, increased morbidity, mortality, and heightened healthcare costs. Understanding the various risk factors contributing to medication-induced hospitalisations is critical for enhancing patient outcomes in healthcare settings. Older patients have been the primary research focus concerning medication induced-hospital admissions, and most of the associated MRPs have been deemed preventable. Medication-related hospital admissions are a substantial concern in Ireland and worldwide. Research findings on the role of age as a risk factor for these admissions have been varied. The aim of this thesis was to explore the association between age and MRP among adult patients in Ireland and internationally. General method This thesis included triangulation between three studies to meet the aim of the thesis. (1) systematic review and meta-analysis, (2) mixed-methods secondary data analysis of the national inpatient experiences survey, (3) mixed-methods content analysis of newspaper articles in Ireland reporting on medication-related harm. (1) Systematic review and meta-analysis The literature about the strength of age as a predictor of MRPs and medication-related admission (MRA) is equivocal. Therefore, the aim of this review was to investigate the association between age and MRA to determine if age is statistically associated with MRA, by undertaking systematic review and meta-analysis. Method A comprehensive electronic search for relevant studies was undertaken in eight databases. All adult patients aged ³16 years were included in this review. The review included all studies that reported hospital admission caused or contributed to by MRAs, including iii | P a g e adverse drug event (ADE), ADR, medication error (ME), and medication non-adherence from the year 2000 that were published in the English language. The Joanna Briggs Institute's (JBI) tool provided by Munn and colleagues from the methodological working group of the Joanna Briggs Institute’s “Methodological guidance for systematic reviews of observational epidemiological studies reporting prevalence and cumulative incidence data” was used, following necessary modifications, to assess the quality of included studies. Only studies with similar data reporting the proportion of each age category and applying the same categorization to age were pooled and analysed using meta-analysis. Results This review identified 48 studies that met the inclusion criteria and were included in the narrative analysis. The total sample size across these included studies was 174,641 patients. There was a meta-analysis generated from this review, comprising 11 studies, aimed to compare the effect size of odds ratios within different age categories within the MRA group. The findings suggest that age is an independent risk factor for MRA in young adults rather than older adults. The quality assessment of the included studies indicated that most studies exhibited moderate quality (n=28). A subset of the remaining studies demonstrated high quality (n=16), while four studies were classified as low quality. Discussion This review concludes that younger adults rather than older adults are at an increased risk of MRA. The findings suggest caution against an overemphasis on older age in policy, practice, or research about managing MRA. Future research should explore the independent risk factors contributing to MRA, to inform associated policy and practice. Moreover, it is recommended that further research use a consistent approach to defining age categories. Additionally, when examining the association between age and MRA, adjustments for confounding factors should be considered. (2) Mixed-methods secondary data analysis of the national patient experience survey Medication experiences can vary significantly from patient to patient, depending on factors such as the patient-, drug- and organisation-related issues. Substantial attention has been focused on understanding medication management experiences among older patients. Yet, evidence remains scarce regarding the medication experiences of younger adults in a hospital setting. The aim of the study was to describe the medication-related experience of iv | P a g e adults receiving inpatient care in Ireland and to explore the association between age and the submission of free text comments describing negative and positive medication experiences. Method This cross-sectional study used secondary data analysis from national patient experiences survey and adopted a sequential explanatory mixed-methods research design. The process involved a comprehensive analysis of both quantitative and qualitative data to enhance understanding of the medication-related experiences of adult inpatients. The quantitative analysis identified the frequency and nature of medication-related experiences and the relationships between demographic or clinical variables and medication-related experience. The free-text responses were qualitatively analysed using thematic analysis to describe the inpatients medication-related experience and to identify targets for improvement. Results The results identified that 1577 (4%) out of 39,453 respondents provided comments related to medication., and most (78.4%) of these comments were negative. Younger patients (aged 16 to 64 years) were significantly more likely than older patients (≥ 65 years) to submit a negative comment. An association was also identified between submission of a negative medication experience and overall rating of hospital experience, suggesting that those who experienced a medication-related problem had a poorer hospital experience overall. The qualitative analysis uncovered several themes including: the professional tasks associated with the patient obtaining their medication, the patient’s sense of safety and security of medication management, transitional care management, receipt of medication information and patient education, and general care about medication. Discussion This secondary analysis identified the challenges faced by adult inpatients with regard to medication during their hospitalisation and at discharge, highlighting the need for better medication processes and communication. Enhancing the quality of prescribing and ensuring that patients receive sufficient information about their medications is crucial. (3) Mixed-methods content analysis of newspapers articles in Ireland reporting on medication-related harm. v | P a g e Mass media, including newspapers, provides a popular and reliable source of health information for the general public. Newspapers are important in disseminating healthrelated news due to their wide readership and easy accessibility. The aim of the study was to describe how MRH, and its association with age, has been reported to the public in Irish newspapers through selected years. Method This content analysis study adopted a sequential explanatory mixed-methods approach. The years 2019, 2009, and 1999 were selected to provide an overview of reporting across three decades. A systematic search strategy was employed using the LexisNexis database to search for medical coverage in Irish newspapers. Quantitative content analysis was used to identify the frequency and nature of MRH reporting, and its association with age. Quantitative thematic content analysis was used to summarise the MRH reporting messages available to the Irish public. Results This study identified 95 MRH patient cases reported in 78 Irish newspaper articles during the years 2019 (n= 68 cases, 51 articles), 2009 (n=20,20), and 1999 (n=7,7). Non-fatal and non-permanent harm was most frequently (56%) reported. Reports of fatal cases had a similar frequency across younger and older adults. Adults aged 16-64 years were the most frequent subject of the reported MRH cases and the most cited medications were the central nervous system medication, antineoplastic and antiparasitic drugs. The four main themes identified were the professional tasks associated with obtaining medications, patient sense of safety and security of the medication management process, medication information and patient education, and general care about medication. Discussion This study identifies an increasing frequency of MRH reporting over-time, about a variety of MRH types and severity, ranging from minor to fatal. The reports provide the public with insights into medication-, patient- and provider-specific issues associated with MRH, and the impacts associated with these. No association between reported MRH and patient age was apparent.
APPROVED